International Law Reform towards the Flood of Future Climate Change Refugees - Athambawa, Mohamed Mowjoon (Indonesian Journal of International Law, 2021)
The popularity of the term “climate change refugees” has been dramatically increasing with the awareness and the disaster of the global warming. The prophecy for mass forced migrations as the consequence of climate change is deplorable. A scandalous statistics revealed that 200 million people would become climate change refugees by 2050. However there is a huge fortification gap in the international legal system which addresses the climate change refugees. Recently academics, lawyers and governments have identified the issues related to climate change refugees and realized the urgency of the formation of policies regarding the protection of the climate change refugees in remedying the plight of this category of the world population. As the first step in handling this dilemma, academics, lawyers, governments and all the stakeholders find it tricky to define the term climate change refugees. Because no one factor, event or process, inevitably results in forced migration and there are a wide range of variables contribute to the definition of the term “climate change refugees”. Different theorists have defined the term differently to distinguish a new category of displaced people. Forced migration and dislocation caused by environmental factors or natural disasters such as earthquakes and floods and man made disasters, such as war and industrial accidents have affected the universe since its existence. Before looking at the international legal constitution, it is necessary to look at the causes of environmentally displaced people in order to offer a complete protection for ‘climate change refugees’. This paper aims to identify who are the ‘climate change refugees’, the gaps in the international legal system which addresses the dilemma of the climate change refugees and proposes a fresh definition for the term “climate change refugees “ and a novel approach for dealing with the plight of this class of people in international legal system.